CURRENT STATE OF ACCOUNTING OF INCOME AND COSTS IN INSURANCE ORGANIZATIONS (American Journal of Business Management, Economics and Banking, 2024)
The article explores the current state of accounting for income and costs in insurance organizations, emphasizing the unique challenges and requirements faced by the industry. It delves into the specific accounting practices adopted by insurance companies, highlighting the importance of accurate financial reporting for regulatory compliance and business sustainability. The study examines the impact of technological advancements, regulatory changes, and global financial standards on the accounting processes within the insurance sector. Through a comprehensive analysis, the article identifies key areas for improvement and suggests best practices to enhance the accuracy and efficiency of income and cost accounting in insurance organizations.